Simultaneous bilateral tibial tubercle avulsion fracture in a male teenager: case report and literature review. Issue 1 (January 2018) - Nicolini, Alexandre P.; Carvalho, Rogerio T.; Ferretti, Mario; Cohen, Moises
Abstract : Tibial tuberosity avulsion fractures are injuries accounting for less than 3% of all epiphyseal and 1% of all physeal injuries in adolescents. Bilateral injuries are very rare, with only 19 cases described in the literature. These types of fractures occur commonly in male teenagers during sport activities and are often associated with other orthopaedic disorders. We report the case of a male teenager with simultaneous bilateral tibial tubercle fractures, describe the evolution and treatment of this injury and review the literature on this subject. Level of evidence: Case report.